2020
DOI: 10.1149/1945-7111/ab6eed
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Activity, Charge Transport, Power Production, and Stability of Commercial Solid Oxide Fuel Cells with Yttria-Stabilized Zirconia Nanoparticles

Abstract: Interconnected networks of 10-30 nm yttria-stabilized zirconia (YSZ) nanoparticles dramatically enhance both the electrocatalytic activity and bulk charge transport of commercial lanthanum strontium manganite (LSM)-YSZ solid oxide fuel cell (SOFC) cathodes. The improvement in both electrode functions increases the maximum power density of the commercial SOFC by 90%. In comparison, modifying cathodes with lanthanum strontium cobalt ferrite (LSCF) and praseodymium barium cobaltite (PBC) nanoparticles, highly act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…These materials simultaneously offer both electronic and ionic conductivity with high transport properties that could result in gaining a high density of electrocatalytic active sites in their structure. In the case of MIEC cathodes, penetrating the oxygen reduction sites into the bulk of the electrodes can extend the oxygen reduction area from the TPBs to the bulk of the cathode, and hence it reduces the cathode polarization losses [50,[56][57][58]. The electronic conductivity of the MIEC composites can be increased by introducing those dopants that could generate oxygen vacancies in the bulk of the material [59].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These materials simultaneously offer both electronic and ionic conductivity with high transport properties that could result in gaining a high density of electrocatalytic active sites in their structure. In the case of MIEC cathodes, penetrating the oxygen reduction sites into the bulk of the electrodes can extend the oxygen reduction area from the TPBs to the bulk of the cathode, and hence it reduces the cathode polarization losses [50,[56][57][58]. The electronic conductivity of the MIEC composites can be increased by introducing those dopants that could generate oxygen vacancies in the bulk of the material [59].…”
mentioning
confidence: 99%
“…Generally, non-stoichiometric oxides with the perovskite structure (ABO 3 ) are classified as a type of MIECs. For example, La x Sr 1−x Co y Fe 1−y O 3−δ (LSCF)-Ce x Gd 1−x O 2−δ (GDC) composite has been reported to be the state-of-the-art cathode MIEC [56]. Wu et al [61] investigated the electrochemical performance of La 1.5 A 0.5 NiO 4+δ (A = Ca, Sr or Ba) cathode materials for intermediate-and low-temperature applications.…”
mentioning
confidence: 99%
“…6 The most common approach has been to infiltrate mixed ionic-electronic conductors (MIECs), such as doped-cerias and doped-cobaltites, into the porous LSM-YSZ electrode, forming nanoparticles of MIECs on the LSM-YSZ surface. [6][7][8][9][10][11] These infiltrant modifications have been shown to lower the cathode reaction impedance and researchers ascribe the improvement to increasing both electrocatalytic activity and the effective density of active sites. [6][7][8][9][10][11] In our own work, we have recently shown that infiltrating YSZ nanoparticles into LSM-YSZ cathodes results in a lower total impedance and higher power density than infiltrating with praseodymium barium cobaltite (PBC) nanoparticles, a highly active MIEC.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11] These infiltrant modifications have been shown to lower the cathode reaction impedance and researchers ascribe the improvement to increasing both electrocatalytic activity and the effective density of active sites. [6][7][8][9][10][11] In our own work, we have recently shown that infiltrating YSZ nanoparticles into LSM-YSZ cathodes results in a lower total impedance and higher power density than infiltrating with praseodymium barium cobaltite (PBC) nanoparticles, a highly active MIEC. 11 Importantly, the nano-YSZ was shown to significantly improve the impedance of both bulk charge transport (35% reduction) and the reaction processes (40% reduction), whereas PBC lowered the reaction impedance by 53% but only lowered the bulk charge transport impedance by 6%.…”
mentioning
confidence: 99%
See 1 more Smart Citation